Diabetes Mellitus Is an Independent Risk Factor for a Stiff Left Atrial Physiology After Catheter Ablation for Atrial Fibrillation - Kim, Moon-Hyun; Yu, Hee Tae; Park, Yoon Jung; Kim, Tae-Hoon; Joung, Boyoung; Lee, Moon-Hyoung; Pak, Hui-Nam (Frontiers in Cardiovascular Medicine, 2022)
Background: Scar tissue formation after catheter ablation for atrial fibrillation (AF) may adversely affect the diastolic properties of the left atrium (LA), which can result in a stiff LA physiology in a small proportion of patients. In this study, we aimed to explore the relationship between diabetes mellitus and a stiff LA physiology after AF catheter ablation (AFCA). Methods: A total of 1,326 patients who underwent de novo AFCA, and baseline and 1-year follow-up echocardiographies were enrolled. After 1:3 propensity score (PS) matching for age, sex, and AF type, we compared 211 patients with DM with 633 patients without DM. A stiff LA physiology was defined as estimated pulmonary arterial pressure increase of >10 mmHg and a right ventricular systolic pressure of >35 mmHg at 1-year follow-up echocardiography. Pulmonary vascular resistance (PVR) was estimated using echocardiographic parameters. Results: Among the 844 PS-matched patients, a stiff LA physiology was observed in 32 patients (4.1%). The patients with DM showed a higher peak LA pressure (p<0.001) and greater LA wall stress (p=0.001) than did those without. A stiff LA physiology was independently associated with DM (Odds ratio [OR]=2.39, 95% confidence interval [CI] 1.02-5.59, p=0.045), empirical extra-pulmonary vein LA ablation (OR=3.14, 95% CI 1.07-9.3, p=0.038) and the delta PVR (OR=1.78, 95% CI 1.37-2.31, p<0.001). The delta PVR was independently associated with DM (beta=0.37, 95% CI 0.06-0.67, p=0.020) and a stiff LA physiology (beta=1.40, 95% CI 0.70-2.10, p<0.001). During the 38.8±29.3months follow-up, the incidence of the clinical recurrence of AF was significantly higher in the patients with a stiff LA physiology than in those without (log rank p=0.032). Conclusion: A stiff LA physiology was independently associated with DM because of the relatively small decrease in the PVR after AFCA in this population. The patients with a stiff LA physiology had worse rhythm outcomes after AFCA than those without.